Pengaruh Model Pembelajaran Treffinger Terhadap Kemampuan Komunikasi Matematis Siswa di SMP Negeri 1 Botomuzoi - Yudika Zebua; Yakin Niat Telaumbanua; Yulisman Zega (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Mathematics is a subject that must be mastered by students at school. But the reality is that SMP Negeri 1 Botomuzoi students suffer from learning difficulties because of the mathematical communication skills of the students who are still in the category. So, the student is unable to communicate his ideas and ideas without the teacher's involvement. The aim of this study was to find out the influence of Trefffinger's learning model on students' mathematical communication skills. This type of research is experimental research using experimental methods (quasy experimental research). The research population was a whole of class VIII students consisting of 4 classes with samples of 2 classes taken by random sampling, namely class VIII-3 as a control class and class VIII-4 as an experimental class. The data is collected by giving the student a mathematical communication skills test that is analyzed by guiding the student's mathematics communication ability test withdrawal. Based on the results of the research, obtained the test of the hypothesis with the value thitung = 11,687 and the value ttable = 1,67. Because thitung > ttable or 11,687>1,67 then reject Ho and accept Ha. which means “There is an effect of Treffinger's learning model on the mathematical communication skills of students in SMP Negeri 1 Botomuzoi